Rage and Resilience: Unveiling Marginalized Voices through Ponni’s Defiance in Saani Kayidham - Sabatini F, Gabriela (Journal of Neonatal Surgery, 2025)
This chapter explores the representation of women’s resistance in south Indian cinema, with a focus on giving voice to marginalized women as portrayed in the film Saani Kayidham. It centers on the themes of systemic oppression, Justice, and human rights. The chapter also examines how the film depicts the struggles of the protagonist ,Ponni. The film narrates Ponni’s journey as she defies societal and institutional barriers to avenge the brutal crimes committed against her and her family. Despite enduring profound emotional, social, and physical trauma, Ponni emerges as a resilient figure, challenging the social upheavals rooted in caste-based discrimination and gender bias. Saani Kayidham presents a compelling critique of a society structured by caste, creed, and status-based judgments of marginalized communities. These structures and constructs perpetuate dehumanization and systemic violence against them. The researcher employs the theoretical framework of intersectionality to highlight the devastating consequences of caste, and class inequities in Southern India. The film effectively portrays the intersection of caste, gender, and socio-economic oppression. This analysis emphasizes the transitional role of Indian cinema in portraying the plight of women’s resilience and resistance. Ponni’s resilience and rage serves as a powerful commentary on women’s safety and the systemic failures of Justice. This chapter also engrossed with the experiences of women who face multiple forms of discrimination, calling for societal introspection and systemic change.